How does distinctive rural development promote farmers’ sustainable income growth? Empirical analysis from northern Jiangsu, China - Chen, Hongqi; Wang, Jing; Chong, Heap-Yih; Jiang, Weimin; Wang, Shanshan (Frontiers in Sustainable Food Systems, 2025)
IntroductionRural areas have actively invested in distinctive rural development by leveraging distinctive rural resources to enhance the vitality and sustainability of farmers’ income growth. However, the pathway to achieve this objective remains uncertain.MethodsThis study focuses on the distinctive rural development in the northern region of Jiangsu Province via a dynamic configurational perspective across three dimensions—agricultural development, tourism cultivation, and cultural infrastructure—within the distinctive industrial system framework on farmers’ income enhancement.Results and discussionThe findings reveal that a single factor is not a necessary condition for promoting farmers’ sustainable income growth; however, low levels of annual income from specialized industries constitute a necessary condition for the maintenance of low-income levels among farmers. There are four combination pathways that drive farmers’ sustainable income growth: Composite Value-Added Driven Type, Agriculture-Oriented E-Commerce Driven Type, Agriculture-Oriented Chain-Based Collaborative Type, and Innovation-Driven Agriculture-Tourism Co-Driven Type. Distinctive rural development not only mitigates the factor constraints associated with traditional income growth pathways but also expands new avenues for increasing income, thereby enhancing farmers’ capacity for income sustained growth. This study advances configurational theory by applying dynamic fsQCA to rural development, highlighting nonlinear factor interactions over isolated variables through a holistic lens on resource endowments and innovations in rural economic systems.